Women in Indian society : a reader - Ghadially, Rehana (Sage Publications, 2011)
The situation of Indian women in a rapidly changing society is examined in this stimulating collection of articles. The contributors explain women's subordination by showing how the traditional and mythical ideas about women are used to control women's lives; and by looking at the various forms of violence towards women, as the immediate context of male domination. The focus is therefore on the objectification of women. Women in Indian Society also describes the growing emergence of women's groups in India and proposes the creation of alternatives through action